Clinical Evaluation of the effectiveness of different bleaching therapies in vital teeth - De Almeida, Letícia Cunha do Amaral Gonzaga [UNESP]; Riehl, Heraldo; Dos Santos, Paulo Henrique [UNESP]; Sundfeld, Maria Lúcia Marçal Mazza [UNESP]; Briso, André Luiz Fraga [UNESP] (My University, 2012)
The aims of this in vivo study were to compare the effectiveness and color stability of at-home and in-office bleaching techniques and to evaluate whether the use of light sources can alter bleaching results. According to preestablished criteria, 40 patients were selected and randomly divided into four groups according to bleaching treatment: (1) at-home bleaching with 10% carbamide peroxide, (2) in-office bleaching with 35% hydrogen peroxide (HP) without a light source, (3) in-office bleaching with 35% HP with quartz-tungsten-halogen light, and (4) in-office bleaching with 35% HP with a lightemitting diode/laser. Tooth shade was evaluated using the VITA Classical Shade Guide before bleaching as well as after the first and third weeks of bleaching. Tooth shade was evaluated again using the same guide 1 and 6 months after the completion of treatment. The shade guide was arranged to yield scores that were used for statistical comparison. Statistical analysis using the Kruskal-Wallis test showed no significant differences among the groups for any time point (P > .01). There was no color rebound in any of the groups. The bleaching techniques tested were equally effective. Light sources are unnecessary to bleach teeth. © 2012 by Quintessence Publishing Co Inc.